Education in Youth Work: in Search for Quality in Youth Non-formal Education - Garbauskaitė-Jakimovska, Justina (Socialinė teorija, empirija, politika ir praktika, 2014)
Summary The main focus of the article is put on the core principles of youth non-formal education (NFE) and their (non)compatibility with the need to improve and maintain the quality of NFE. The aim for quality is a priori legitimate in the liberal societies in all spheres of life. Nevertheless the means for quality improvement often have authoritarian, restrictive, formalising or standardising characteristics that are not compatible with main values, principles and aims of non-formal education: freedom, voluntarism and development of a conscious individual. The article describes the phenomenon of non-formal education in European and Lithuanian contexts, the concept and criteria of quality in non-formal education and existing practices for quality improvement are analysed. Key words: youth non-formal education, quality, recognition, liberty.